Morphometric and carcass quality of chinchilla rabbits slaughtered at defined age (2010)
A total of twelve (90 days old) Chinchilla rabbits with an average live weight of 1.28-1.30kg were used to evaluate the effect of sex on morphometric, carcass and meat quality of rabbits. Two treatment groups of male and female were employed and each treatment was replicated thrice in a completely randomized design. The rabbits were stunned mechanically, exsanguinated and properly bled. After bleeding the rabbits were skinned and cut into two equal halves. Body morphometric indices such as body length, forelimb length, head length, head width and chest depth were measured and it’s result showed that apart from the head width, chest depth and pelvis depth that were significantly higher in female, other body measurement were similar (p>0.05) in both sexes. Water holding capacity was higher in males than in females with values of 76.33 to 70.00 % for shoulder in male and female respectively. The thigh of the male has a value of 80.00 as against 75.00% for the female. The dressing percentage were higher in male (p>0.05) with a value of45.50% to 41.99% in the female. The taste panelists rated meat from both sexes similar (p>0.05) in all parameters.